PENGARUH PENAMBAHAN SERBUK BAN BEKAS UNTUK BAHAN TAMBAH CAMPURAN ATB (ASPHALT TREATED BASE) - Blima Oktaviastuti; Handika Setya Wijaya; Prana Indrawan (Universitas Tribhuwana Tunggadewi Malang, 2018)
The growing need of motor vehicles each year must be balanced with the supporting facilities. Roads to support the smooth driving of using motor vehicles, always require maintenance in case of damage. The need for materials for road construction every year will always increase, one of them asphalt needs. Therefore, some alternative waste utilization is needed so that the asphalt needs can be fulfilled. A lot of waste that can be used as a mixture of asphalt, one of which used tires every year is always increasing in number. The objectives of this research are: (1) To know Marshall parameters from 0%, 1.5%, 3%, 4,5%, and 6% of used tire waste, and (2) To know the additional level of waste the best used tires as additives to the ATB mixture are reviewed against stability. This research uses a quantitative method approach with experimental research design. The research design includes several stages: aggregate material, tire powder, and asphalt, then the stage of making the specimens to determine the optimum asphalt content with 4%, 4.5%, 5%, 5.5%, 6 %, 6.5%, after it was found that the optimum bitumen content was then subjected to the manufacture of test specimens with the addition of used tire powder with a range of 0%, 1.5%, 3%, 4.5%, 6% of the weight of the aggregate. The results of the research are: (1) the increasing number of used tire powder tends to decrease the stability value, (2) the addition of the best tire powder is at the tire powder level of 1.5% by obtaining a stability value of 1293 kg.